2005
DOI: 10.1002/jbm.b.30382
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural and crystallographic surface changes after grinding zirconia‐based dental ceramics

Abstract: The purpose of this study was to evaluate microstructural and crystallographic phase changes after grinding 3Y-TZP dental ceramics. Ceramic blanks were sintered according to manufacturer's recommendations and divided into four groups: (A) as-sintered control, (B) diamond-ground manually under water, (C) ground and polished, and (D) ground and annealed at 1000 degrees C for 1 h. Bulk specimens were analyzed by X-ray diffraction to characterize the crystalline phases. The microstructure was investigated by SEM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
119
1
7

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 146 publications
(138 citation statements)
references
References 33 publications
11
119
1
7
Order By: Relevance
“…However, other studies 38) have verified that grinding without irrigation would favor the zirconia through a reverse phase transformation (m→t), due to the localized generated heat, and that the t phase could increase the flexural resistance of the zirconia 28) . In this study it was observed that grinding, irrespectively of DG or WG, promoted a reverse phase transformation (m→t) when compared with the control group, with WG group being responsible for the greater transformation of monoclinic grains into tetragonal (Tables 1 and 2). SEM images (Figs.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…However, other studies 38) have verified that grinding without irrigation would favor the zirconia through a reverse phase transformation (m→t), due to the localized generated heat, and that the t phase could increase the flexural resistance of the zirconia 28) . In this study it was observed that grinding, irrespectively of DG or WG, promoted a reverse phase transformation (m→t) when compared with the control group, with WG group being responsible for the greater transformation of monoclinic grains into tetragonal (Tables 1 and 2). SEM images (Figs.…”
Section: Discussionmentioning
confidence: 98%
“…X-ray diffraction has been often used to quantify the crystalline zirconia phases; however some inconsistent results regarding the peaks of tetragonal, cubic and monoclinic phases have been continuously referred and compared among papers [26][27][28][29] . In this study, the presintered specimens showed tetragonal and monoclinic phases in an amount allowed by the ISO 13356 30) .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a consequence, tremendous efforts have been made to investigate material removal mechanism and the corresponding surface and subsurface damages during grinding of difficult-to-machine material such as alumina [8], silicon nitride [9][10][11][12], zirconia [13], glasses [14,15], and particulate reinforced titanium matrix composites [16,17]. Specific to silicon carbide ceramics, Agarwal et al [18] conducted a high machining rate grinding experiments to study the surface/ subsurface damage formation and material removal mechanism.…”
Section: Introductionmentioning
confidence: 99%